Experimental study on horizontal cylinders with triangular fins under natural convection - Lee, Gu Won; Kim, Hyun Jung; Kim, Dong Kwon (Energies, 2018)
In this study, thermal resistances of horizontal cylinders with triangular fins were measured in regard to fin numbers, fins heights, and temperature differences. Thereafter, an empirical correlation was proposed and validated for predicting the Nusselt numbers under the following conditions: Rayleigh number, 200,000-1,000,000; fin aspect ratio, 1.6-5.0; and fin number, 9-72. Finally, with the proposed correlation, the effects of fin numbers, fins heights, and fin thicknesses on the thermal resistances of the horizontal cylinders with triangular fins were investigated. It was shown that the thermal resistance generally increases as the fin number, fin height, and fin thickness increase. It is expected that horizontal cylinders for various cooling devices with triangular fins can be designed based on the findings of the present study.
Keywords: Cooling devices; Empirical correlations; Fin numbers; Fin thickness; Finned cylinder; Horizontal cylinders; Rayleigh number; Temperature differences; Finned cylinders; Natural convection; Nusselt number